An Analysis of Language Style Used in The Late-Late Show with James Corden - Septi Dwi Marheni; Rosita Ambarwati; Tri Wahyuni Chasanatun (Linguista: Jurnal Ilmiah Bahasa, Sastra, dan Pembelajarannya, 2022)
This study discusses about the use of language style in talk show “The Late-Late Show with James Corden”. The researcher use three videos taken from The Late-Late Show with James Corden, those are the video  entitled ‘Bill Gates Knows 'How to Avoid a Climate Disaster' ,  “How Did Adele Get Celine Dion's Gum from James?’and the video entitled “Jackson Wang: LMLY” . This study aims to identify and describe the types of language style and also social context in he Late-Late Show with James Corden. This study used theory of Joos (1967)  to analyze the type of language style and the theory from Holmes (2013) to analyze the social context. This study used descriptive qualitative approach, and for processing the data using the theory from Miles & Huberman (1994). The result of this study that the researcher found are 114 data. Then, there are 12  or 11% of the data which is categories as formal style. There are 14 or 12% of the  data  which is categories  as consultative style. There are 88 or 77% of the data which is categories as casual style. So, the dominant type used in The Late-Late Show with James Corden is casual style. The use of language style influenced by social context those are participant in the interaction, setting or social context of interaction, topic of interaction and function of interaction.